Adhesive and adhesive sheet
Patent Information
- Application Number
- CN202311163122.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-08
- Filing Date
- 2020-04-17
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2040-04-17
AI Technical Summary
Existing polyester adhesives have poor workability and insufficient dent resistance after being cut into smaller sizes. They also have insufficient adhesion to the substrates they are bonded to, especially to plastic substrates, making it difficult to meet the requirements of protective components for the display of portable electronic devices.
A polyester resin with high bioplasticity is generated using plant-derived raw materials such as dimer acids, sebacic acid, and dimer diols. The resin is then cross-linked to form an adhesive. Diols with an even number of carbon atoms are used to increase the ester group concentration, ensuring high adhesion, excellent processability, dent resistance, and transparency.
It achieves good adhesion to various substrates, has excellent processability and dent resistance, and is suitable for small adhesive sheets, especially protective components for the display of portable electronic devices.
Smart Images

Figure BDA0004441177310000341 
Figure BDA0004441177310000351 
Figure BDA0004441177310000381
Abstract
Description
[0001] This application is a divisional application of the patent application filed on April 17, 2020, with application number 202080030307.X and invention title "Adhesive and Adhesive Sheet". Technical Field
[0002] This invention relates to polyester-based adhesives and adhesive sheets, and more specifically, to adhesives and adhesive sheets that use plant-derived raw materials that are environmentally friendly and have good adhesion to various adhered materials such as metals and plastics, as well as excellent processability, dent resistance, and transparency. Background Technology
[0003] In recent years, from the perspective of miniaturization and lightweighting of products, adhesives have been increasingly used in the joining of parts, etc. As such adhesives, adhesives using polyester resins with excellent adhesion have also been studied.
[0004] On the other hand, recently, as part of countermeasures against the depletion of fossil resources and global warming, the use of plant-derived raw materials, which are renewable resources, has been recommended, and adhesives with high bioplasticity using plant-derived raw materials that are environmentally friendly to the earth are being sought.
[0005] Patent document 1 discloses a low moisture permeability adhesive sheet having an adhesive layer formed from a polyester-based adhesive using this plant-derived raw material, and having a moisture permeability of 200 g / m³. 2 The following describes a polyester adhesive containing a polyester polymer with alkyl groups on its molecular side chains, obtained by condensing plant-derived dicarboxylic acids with plant-derived diols.
[0006] In addition, Patent Document 2 proposes an adhesive sheet using a polyester containing at least lactic acid units, diacid units, and diol units, wherein the diacid units contain dimer acids. For the aforementioned polyester, the glass transition temperature is -70 to -20°C, the weight-average molecular weight is 20,000 to 300,000, and the hydroxyl value is 1 to 100 mg KOH / g when measured using a differential scanning calorimeter at a heating rate of 20°C / min.
[0007] Typical polyester resins are crystalline, but in adhesive applications, it becomes important to break down their crystallinity.
[0008] Existing technical documents
[0009] Patent documents
[0010] Patent Document 1: Japanese Patent Application Publication No. 2007-308626
[0011] Patent Document 2: Japanese Patent Application Publication No. 2010-37463 Summary of the Invention
[0012] The problem the invention aims to solve
[0013] However, the technology disclosed in Patent Document 1 uses long-chain alkyl-based raw materials, resulting in a polyester resin that is very soft. Therefore, although it is a bioplasticity-high and environmentally friendly adhesive, its softness makes it very difficult to handle when making tapered adhesive sheets. Furthermore, the resin itself is too soft, making it difficult to perfectly produce adhesive sheets before crosslinking. In addition, the adhesive has poor dent resistance, requiring further improvement to balance environmental impact with adhesive performance.
[0014] It should be noted that, for example, for adhesive sheets used to fix the protective components (such as glass covers) of the display section of portable electronic devices, it is very important to make the adhesive sheets smaller from the perspective of increasing the size of the information display section, improving design, and increasing design freedom.
[0015] Making the adhesive sheet thinner increases the difficulty of handling it. While thinning reduces the surface area of the adhesive sheet, the area of the exposed adhesive on the sides remains unchanged, even with a release liner, making handling more challenging. Furthermore, thinning the adhesive sheet necessitates cutting it, but the increased cutting width can lead to stretching of the adhesive layer with the cutter, negatively impacting the sheet's performance. Additionally, the adhesive may adhere to the blade, reducing machinability and workability.
[0016] Furthermore, for thin adhesive sheets used in protective components for displays of portable electronic devices, there is a requirement for adhesive sheets that do not become sticky on the sides, do not deform when cut, and have minimal adhesion to the blade. Moreover, there is a requirement for adhesives with excellent dent resistance to external forces on the adhesive layer, and excellent transparency to detect abnormalities such as foreign object intrusion.
[0017] Although the technology disclosed in the aforementioned Patent Document 2 has yielded an adhesive with high bioplasticity and environmental friendliness, it is still insufficient in terms of the adhesive properties of the adhered objects. In particular, it is not sufficient to achieve the required balance between holding force and adhesive force for double-sided tapes, or it does not meet the requirements for the adhesive properties of plastic substrates, especially polyolefin substrates, which are not easy to bond. Further improvements are needed.
[0018] Furthermore, the polylactic acid-based polyester disclosed in the aforementioned patent document 2 is expected to be a plant-derived material, but it is prone to hydrolysis and is very difficult to use as an adhesive with high requirements for damp heat durability, so it is not desirable to use it.
[0019] Therefore, in this context, the present invention provides adhesives and adhesive sheets that are made from plant-derived raw materials that are environmentally friendly, have good adhesion to various adhered objects, excellent processability, dent resistance, and transparency.
[0020] Solution for solving the problem
[0021] Therefore, the inventors have discovered that when a polyester resin with high bioplasticity is generated by using at least one of plant-derived raw materials such as dimer acids, sebacic acids, and dimer diols, and an adhesive composition containing the polyester resin is crosslinked to manufacture an adhesive, using a diol component with an even number of carbon atoms as the polyol component constituting the polyester resin increases the ester group concentration of the polyester resin, thereby setting a higher specified adhesive strength. As a result, an adhesive that is environmentally friendly, has good adhesion properties to various adhered objects, and exhibits excellent performance even after fine-width processing, dent resistance, and transparency can be obtained.
[0022] That is, the first objective of the present invention is to provide an adhesive, which is an adhesive obtained by crosslinking an adhesive composition, said adhesive composition containing a polyester resin (i), said polyester resin (i) having structural sites derived from polycarboxylic acids (a) and structural sites derived from polyol components (b).
[0023] The aforementioned polyester resin (i) contains at least 60% by weight of structural sites derived from at least one of the group consisting of dimer acids, sebacic acids, and dimer diols, relative to the polyester resin (i).
[0024] A diol (b1) containing an even number of carbon atoms (excluding dimer diols) is included as the polyol component (b) above.
[0025] The ester group concentration of the above-mentioned polyester resin (i) is 2 mmol / g or more.
[0026] The adhesive force (α) under the following conditions is 1 N / 25 mm or more.
[0027] Adhesive strength (α): When an adhesive sheet with an adhesive layer formed by an adhesive on a substrate is made, the 180-degree peel strength (N / 25mm) of the adherend after being placed on a SUS-BA board at 23°C and 50%RH for 30 minutes, at a peel speed of 300 mm / min.
[0028] Furthermore, a second objective of the present invention is to provide an adhesive obtained by crosslinking an adhesive composition, said adhesive composition containing a polyester resin (ii) with a bioplasticity of 60% or more.
[0029] The aforementioned polyester resin (ii) has structural sites derived from polycarboxylic acids (a) and structural sites derived from polyol components (b), and contains a diol (b1) with an even number of carbon atoms (excluding dimer diols) as the aforementioned polyol component (b).
[0030] The ester group concentration of the above-mentioned polyester resin (ii) is 2 mmol / g or higher.
[0031] The adhesive force (α) under the following conditions is 1 N / 25 mm or more.
[0032] Adhesive strength (α): When an adhesive sheet with an adhesive layer formed by an adhesive on a substrate is made, the 180-degree peel strength (N / 25mm) of the adherend after being placed on a SUS-BA board at 23°C and 50%RH for 30 minutes, at a peel speed of 300 mm / min.
[0033] Furthermore, in this invention, the third objective is to provide an adhesive sheet having an adhesive layer containing the adhesive described in the first or second objective.
[0034] Typically, raw materials with high bioplasticity are long-chain alkyl groups, such as sebacic acid derived from castor oil, dimer acids derived from oleic acid, and dimer diols utilizing these dimer acids. For example, sebacic acid is a highly crystalline monomer used in the formation of polyester resins, and polyester resins derived from sebacic acid are used as crystalline polyester resins. On the other hand, dimer acids and dimer diols are monomers used for softening and water resistance of resins. To improve their physical properties, it is advantageous to have an extremely low ester group concentration; therefore, it is preferable to minimize the ester group concentration.
[0035] Furthermore, when making adhesives from polyester resins, it is generally necessary to lower the glass transition temperature. Therefore, alkyl dicarboxylic acids and diols containing alkyl groups with 5 or more carbons, such as neopentyl glycol (5 carbons), are often used to disrupt crystallinity, while some long-chain diols, such as 1,6-hexanediol (6 carbons), are used for softening. These diols disrupt the crystallinity of polyester resins, lower the glass transition temperature, and thus improve adhesive strength. Using diols with fewer carbons, i.e., diols with 4 or fewer carbons, results in insufficient flexibility and compromised adhesive properties; therefore, diols with 4 or fewer carbons are generally not considered as the main component.
[0036] However, in this invention, although it is unexpectedly a polyester resin with high bioplasticity, the diol with an even number of carbon atoms is used as the polyol component to improve the molecular arrangement, and it is designed to not actually cause crystallization. Furthermore, the ester group concentration is increased while using plant-derived long-chain monomers, thereby achieving the purpose of this invention.
[0037] For example, when an adhesive is made from a polyester resin with dimeric acid and dimeric diol as the main components, it becomes a very soft resin due to the influence of its long main chain and alkyl side chains, resulting in significantly poor "dent resistance during adhesive sheet molding" and "processability such as when cutting the finished adhesive sheet to the required size". In this invention, for example, dimeric acid and suitable sebacic acid are used to make it soft, and on the other hand, small diols such as ethylene glycol and 1,4-butanediol are used as diols to maximize the concentration of ester bonds as hard components, thereby improving the dent resistance and processability of the adhesive made from the polyester resin.
[0038] Furthermore, for example, compared to using diols with an odd number of carbons, such as 1,3-propanediol, it is believed that using diols with an even number of carbons, such as ethylene glycol and 1,4-butanediol, results in a structure where a portion of the polymer chain is arranged more easily, increasing the cohesive force within the resin. As a result, it is speculated that the adhesive force required for the double-sided tape will further increase.
[0039] The effects of the invention
[0040] The adhesive of the present invention is an adhesive obtained by crosslinking an adhesive composition, wherein the adhesive composition contains a polyester resin (i), the polyester resin (i) having structural sites derived from a polycarboxylic acid (a) and structural sites derived from a polyol component (b), the polyester resin (i) containing at least 60% by weight of structural sites derived from at least one of the group consisting of dimer acids, sebacic acids and dimer diols, and containing a diol (b1) with an even number of carbon atoms (excluding dimer diols) as the polyol component (b), the ester group concentration of the polyester resin (i) being 2 mmol / g or more, and the adhesive strength (α) under the above conditions being 1 N / 25 mm or more. Therefore, it becomes an adhesive with high bioplasticity and environmental friendliness, and the polyester resin containing a high ester group concentration has good adhesion to various adhered materials, and also has excellent processability, dent resistance, and transparency when cut into smaller pieces.
[0041] Therefore, it is effectively used for single-sided or double-sided adhesive sheets for bonding optical components, for fixing components of portable electronic devices, and for fixing electronic components.
[0042] If the diol (b1) with an even number of carbon atoms is an aliphatic diol with a straight-chain structure, it can form an adhesive with excellent balance between crystallinity and aggregation.
[0043] If the above polycarboxylic acid (a) contains less than 70 mol% of straight-chain carboxylic acid (a1), an adhesive with a better balance between crystallinity and aggregation can be formed.
[0044] If the above polyol component (b) contains 10 to 100 mol% of diols (b1) with an even number of carbon atoms, an adhesive with superior adhesion can be formed.
[0045] If the diol (b1) with an even number of carbon atoms is a polyol with 4 or fewer carbon atoms, it can form an adhesive with excellent stability.
[0046] If the acid value of the above-mentioned polyester resin (i) is less than 10 mg KOH / g, an adhesive with excellent durability can be formed.
[0047] If the bioplasticity of the aforementioned polyester resin (i) is above 60%, it can form an adhesive that is more environmentally friendly.
[0048] Furthermore, the adhesive of the present invention is an adhesive obtained by crosslinking an adhesive composition, wherein the adhesive composition contains a polyester resin (ii) with a bioplasticity of 60% or more, the polyester resin (ii) having structural sites derived from polycarboxylic acids (a) and structural sites derived from polyol components (b), and containing a diol (b1) with an even number of carbon atoms (excluding dimer diols). The ester group concentration of the polyester resin (ii) is 2 mmol / g or more, and the adhesive strength (α) under the aforementioned conditions is 1 N / 25 mm or more. Therefore, it becomes an adhesive with high bioplasticity and environmental friendliness, and the polyester resin containing a high ester group concentration has excellent adhesion to various adhered materials, excellent processability when thinned, excellent dent resistance, and excellent transparency.
[0049] Therefore, it is effectively used for single-sided or double-sided adhesive sheets for bonding optical components, for fixing components of portable electronic devices, and for fixing electronic components.
[0050] If the above adhesive composition also contains a hydrolysis inhibitor (iii), an adhesive with excellent long-term durability can be formed.
[0051] If the above adhesive composition also contains a crosslinking agent (iv), an adhesive with even better adhesion can be formed.
[0052] If the above adhesive composition also contains a tackifying resin (vii), an adhesive with even better adhesive properties can be formed.
[0053] In addition, if the bioplasticity of the adhesive is above 60%, it can form an adhesive that is more environmentally friendly to the earth. Detailed Implementation
[0054] The structure of the present invention will now be described in detail, but these descriptions illustrate one example of an ideal implementation.
[0055] It should be noted that, in this invention, the term "carboxylic acid class" includes not only carboxylic acids but also carboxylic acid hydrogenates, carboxylic acid salts, carboxylic anhydrides, carboxylic acid halides, carboxylic acid esters, and other carboxylic acid derivatives.
[0056] The adhesive composition forming the adhesive of the present invention contains a polyester resin (i), said polyester resin (i) having structural sites derived from a polycarboxylic acid (a) and structural sites derived from a polyol component (b), said polyester resin (i) containing at least 60% by weight of structural sites derived from at least one of the group consisting of dimer acids, sebacic acids and dimer diols relative to the polyester resin (i), and containing a diol (b1) with an even number of carbon atoms (excluding dimer diols) as the polyol component (b), and the ester group concentration of the polyester resin (i) is 2 mmol / g or more.
[0057] Furthermore, the adhesive composition forming the adhesive of the present invention contains a polyester resin (ii) with a bioplasticity of 60% or more, wherein the polyester resin (ii) has a structural site derived from a polycarboxylic acid (a) and a structural site derived from a polyol component (b), and contains a diol (b1) with an even number of carbon atoms (excluding dimer diols) as the polyol component (b), and the ester group concentration of the polyester resin (ii) is 2 mmol / g or more.
[0058] The components constituting the adhesive composition of the present invention will be described in turn below.
[0059] <Polyester-based resins (i), (ii)>
[0060] The polyester resins (i) and (ii) used in this invention have structural sites derived from polycarboxylic acids (a) and structural sites derived from polyol components (b), for example, obtained by copolymerizing a copolymer containing polycarboxylic acids (a) and polyol components (b).
[0061] [Polycarboxylic acids (a)]
[0062] In this invention, to improve bioplasticity, plant-derived polycarboxylic acids are preferred.
[0063] Examples of polycarboxylic acids derived from the aforementioned plants include sebacic acids from castor oil, dimer acids derived from oleic acid, linoleic acid, linolenic acid, erucic acid, etc. (mainly with carbon numbers of 36 and 44), and succinic acids from glucose. It should be noted that, in addition to plant sources, dimer acids derived from butter can also be used as examples of the aforementioned dimer acids.
[0064] In addition, among polycarboxylic acids (a), straight-chain carboxylic acids (a1) are preferred in terms of ease of obtaining raw materials and ease of manufacturing, straight-chain carboxylic acids with 4 to 12 carbon atoms are more preferred, and straight-chain carboxylic acids with 6 to 10 carbon atoms are even more preferred. Sebacic acid is particularly preferred in terms of lowering the glass transition temperature and easy adjustment of adhesive properties.
[0065] The polyester resins (i) and (ii) used in this invention contain structural sites derived from polycarboxylic acids (a). Preferably, the polycarboxylic acid (a) contains 70 mol% or less of a linear carboxylic acid (a1), particularly preferably 5 to 70 mol%, and even more preferably 10 to 60 mol%. Excessive content of these components tends to increase crystallinity. Conversely, insufficient content tends to decrease manufacturing stability.
[0066] In addition, as a polycarboxylic acid (a), a dimer acid (a2) is preferred in order to easily prevent the crystallization of polyester resins, and hydrogenated dimer acids are preferred.
[0067] The dimer acid (a2) mentioned above preferably contains 40 mol% or more, particularly preferably 50 mol% or more, and even more preferably 60 mol% or more, relative to the polycarboxylic acid (a). It should be noted that the upper limit is usually 100 mol%. If the above content is too low, there is a tendency for crystallinity to increase.
[0068] As the aforementioned polycarboxylic acid class (a), it is also preferred to use a combination of a straight-chain carboxylic acid class (a1) and a dimer acid class (a2). When they are used in combination, the molar ratio of (a1):(a2) is preferably 1:99 to 90:10, more preferably 5:95 to 60:40, and particularly preferably 10:90 to 50:50.
[0069] It should be noted that polycarboxylic acids other than those described above may be used within the scope that does not impair the purpose of the present invention.
[0070] Examples of polycarboxylic acids other than those mentioned above include: malonic acid derivatives, dimethylmalonic acid derivatives, glutaric acid derivatives, adipic acid derivatives, trimethyl adipic acid derivatives, heptaic acid derivatives, 2,2-dimethylglutaric acid derivatives, azelaic acid derivatives, fumaric acid derivatives, maleic acid derivatives, itaconic acid derivatives, thiodipropionic acid derivatives, diethanolic acid derivatives, and 1,9-nonanedicarboxylic acid derivatives (aliphatic dicarboxylic acids); phthalic acid derivatives, terephthalic acid derivatives, isophthalic acid derivatives, benzylmalonic acid derivatives, biphenyl acid derivatives, and 4,4'-oxobisphenyl acid derivatives. Aromatic dicarboxylic acids, such as formic acid derivatives, 1,8-naphthalenedicarboxylic acid derivatives, 2,3-naphthalenedicarboxylic acid derivatives, 2,7-naphthalenedicarboxylic acid derivatives, etc.; alicyclic dicarboxylic acids, such as 1,3-cyclopentanedicarboxylic acid derivatives, 1,2-cyclohexanedicarboxylic acid derivatives, 1,3-cyclopentanedicarboxylic acid derivatives, 1,4-cyclohexanedicarboxylic acid derivatives, 2,5-norbornenedicarboxylic acid derivatives, adamantanedicarboxylic acid derivatives, etc.; trimethylbenzene tricarboxylic acid derivatives, pyromellitic acid derivatives, adamantane tricarboxylic acid derivatives, pyromellitic acid derivatives, etc., which are tri- or higher carboxylic acids.
[0071] The above-mentioned polycarboxylic acids (a) can be used in one or in combination of two or more.
[0072] [Polyol component (b)]
[0073] In this invention, plant-derived polyols are preferably used to improve bioplasticity.
[0074] Examples of polyols derived from the aforementioned plants include: fatty acid ester diols derived from castor oil; dimer acids (mainly with 36 or 44 carbon atoms) derived from oleic acid, linoleic acid, linolenic acid, erucic acid, etc.; dimer diols formed by the diolization of their hydrogenated derivatives; bioethylene glycol; biopropylene glycol; and biobutanediol. Among these, bioethylene glycol and biopropylene glycol (1,3-propanediol) are preferred for their ability to easily increase ester group concentration, with bioethylene glycol being particularly preferred.
[0075] In this invention, as the polyol component (b), from the perspective of imparting aggregation force by simultaneously disrupting crystallinity and improving molecular arrangement, a diol (b1) with an even number of carbon atoms must be used (excluding dimer diols).
[0076] Examples of aliphatic diols (b1) with an even number of carbon atoms include: ethylene glycol, diethylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,8-octanediol, 1,10-decanediol, 1,12-dodecanediol, etc., which have straight-chain aliphatic diols; and 1,2-butanediol, 1,3-butanediol, dipropylene glycol, 2,4-dimethyl-2-ethylhexane-1,3-diol, 2-methyl-1,3-propanediol, 3-methyl-1,5-pentanediol, etc., which have branched-chain aliphatic diols.
[0077] Alicyclic diols such as 1,2-cyclohexanediethanol, 1,3-cyclohexanediethanol, 1,4-cyclohexanediethanol, tricyclodecanediethanol, adamantanediol, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol;
[0078] 4,4'-Thiodiphenol, bisphenol S, 4,4'-dihydroxybiphenyl, o-dihydroxybenzene, m-dihydroxybenzene, p-dihydroxybenzene, 2,5-naphthalenediol, p-xylenediol and other aromatic diols; and their ethylene oxide and propylene oxide adducts;
[0079] wait.
[0080] For the diols (b1) with an even number of carbon atoms mentioned above, plant sources are preferred.
[0081] Among the diols (b1) with an even number of carbon atoms, aliphatic diols are preferred. From the perspective of balancing crystallinity and aggregation, aliphatic diols with a straight-chain structure are particularly preferred.
[0082] In addition, from the perspective of improving ester bond concentration and manufacturing stability, diols with an even number of carbons (b1) are preferably diols with 4 or fewer carbons, and diols with 2 carbons are particularly preferred.
[0083] As a preferred specific example of a diol (b1) with an even number of carbons used in this invention, aliphatic diols with a straight chain structure and fewer than 4 carbons, such as ethylene glycol, diethylene glycol, and 1,4-butanediol, can be cited. Ethylene glycol and 1,4-butanediol are preferred, and ethylene glycol is particularly preferred.
[0084] In this invention, the content of the diol (b1) with an even number of carbon atoms is preferably 10 to 100 mol%, particularly preferably 30 to 99.9 mol%, further preferably 50 to 99.7 mol%, and especially preferably 70 to 99.6 mol%, relative to the total polyol component (b). If the above content is too low, there is a tendency for the adhesive properties to decrease.
[0085] It should be noted that, in this invention, polyol components (b) other than the diols (b1) with an even number of carbon atoms may be used without compromising the purpose of this invention.
[0086] As for polyol components (b) other than diols with an even number of carbon atoms (b1) mentioned above, examples include diols with an odd number of carbon atoms, polyols with three or more carbon atoms, etc.
[0087] Examples of aliphatic diols with an odd number of carbon atoms include: 1,3-propanediol, 1,5-pentanediol, 1,9-nonanediol, etc., which have a straight-chain aliphatic diols; 2,2-dimethyl-1,3-propanediol (neopentanediol), 2-ethyl-2-butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 2,2,4-trimethyl-1,6-hexanediol, etc., which have a branched-chain aliphatic diols.
[0088] Spirocyclic diols and other alicyclic diols;
[0089] 4,4'-Methylenediphenol, bisphenol A, bisphenol fluorene and other aromatic diols; and their ethylene oxide and propylene oxide adducts;
[0090] wait.
[0091] Examples of polyols with three or more components include: pentaerythritol, dipentaerythritol, tripentaerythritol, glycerol, trimethylolpropane, trimethylolethane, 1,3,6-hexanetriol, and adamantine triol.
[0092] In terms of improving crystallinity and solution stability, diols with an odd number of carbon atoms are preferred, and aliphatic diols with branched structures are more preferred. From a general perspective, 2,2-dimethyl-1,3-propanediol (neopentyl glycol) and 2-ethyl-2-isobutyl-1,3-propanediol are preferred.
[0093] Furthermore, regarding the polyol component (b) mentioned above, if the polycarboxylic acid (a) has high bioplasticity, from the perspective of ease of polycondensation, a polyol component not derived from plants can also be used. However, in this case, to improve bioplasticity, it is preferable to use a polyol with 4 or fewer carbon atoms, and particularly preferable to use a polyol with 2 carbon atoms. That is, this is because when a polyol component (b) with fewer than 4 carbon atoms is used, the weight ratio of the carboxylic acid (a) with high bioplasticity increases as a polyester resin (i) and (ii), thereby improving bioplasticity. Specific examples of polyols with 4 or fewer carbon atoms include ethylene glycol and 1,4-butanediol.
[0094] The above-mentioned polyol component (b) can be used in one or in combination of two or more.
[0095] In addition to the polyol component (b) and polycarboxylic acid (a) mentioned above, compounds that have both carboxylic acid and hydroxyl groups in the molecule (such as lactic acid) may also be used within a range that does not impair the effects of the present invention. However, lactic acid is prone to hydrolysis, so it is more preferable not to use it.
[0096] In order to achieve high bioplasticity, the polyester resins (i) and (ii) used in this invention preferably contain at least 60% by weight or more of the copolymer component selected from the group consisting of dimer acids, sebacic acids, and dimer diols, more preferably 65% by weight or more, further preferably 70% by weight or more, and particularly preferably 80% by weight or more, relative to the copolymer component of the polyester resins (i) and (ii). It should be noted that the upper limit is 100% by weight. If the above content is low, the resulting polyester resins (i) and (ii) tend to have lower bioplasticity, and the reduction in environmental impact becomes insufficient.
[0097] [Manufacturing of polyester resins (i) and (ii)]
[0098] In this invention, polyester resins (i) and (ii) can be manufactured by polycondensation of a polycarboxylic acid (a) and a polyol component (b) in the presence of a catalyst using a known method. During the polycondensation reaction, esterification or transesterification is performed first, followed by polycondensation. It should be noted that, in cases where high molecular weight formation is not required, esterification or transesterification may be used alone to manufacture the resins.
[0099] In the aforementioned esterification or transesterification reactions, catalysts are typically used. Specifically, examples include titanium-based catalysts such as tetraisopropyl titanate and tetrabutyl titanate, antimony-based catalysts such as antimony trioxide, germanium-based catalysts such as germanium dioxide, zinc acetate, manganese acetate, and dibutyltin oxide. One or two of these catalysts can be used. Among these, antimony trioxide, tetrabutyl titanate, germanium dioxide, and zinc acetate are preferred due to their catalytic activity and the desired color balance of the resulting reactants.
[0100] The amount of the catalyst mixed with the above catalyst relative to the total copolymer components (by weight) is preferably 1 to 10,000 ppm, particularly preferably 10 to 5,000 ppm, and even more preferably 20 to 3,000 ppm. If the above amount of catalyst is too small, the polymerization reaction may not proceed sufficiently; even if it is too large, it does not have the advantage of shortening the reaction time and may easily cause side reactions.
[0101] The preferred reaction temperature for esterification is 200–300°C, particularly preferred is 210–280°C, and even more preferred is 220–260°C. If the reaction temperature is too low, the reaction may not proceed sufficiently; if it is too high, side reactions such as decomposition may easily occur. Furthermore, the reaction pressure is typically atmospheric pressure.
[0102] As for the reaction conditions for the polycondensation reaction following the aforementioned esterification or transesterification reaction, it is preferable to further mix in the same amount of the same catalyst used in the aforementioned esterification or transesterification reaction, and to set the reaction temperature preferably to 220–280°C, particularly preferably 230–270°C, and to slowly reduce the pressure of the reaction system, ultimately reacting at a pressure below 5 hPa. If the above reaction temperature is too low, the reaction tends to be difficult to proceed completely; if it is too high, it tends to easily cause side reactions such as decomposition.
[0103] Thus, the polyester resins (i) and (ii) used in this invention are obtained.
[0104] In order to achieve high bioplasticity, the polyester resin (i) used in this invention should contain at least 60% by weight of structural portions derived from at least one of the group consisting of dimer acids, sebacic acids, and dimer diols, preferably at 65% by weight or more, more preferably at 70% by weight or more, and particularly preferably at 80% by weight or more. It should be noted that the upper limit is 100% by weight. If the content of the above-mentioned structural portions is low, the bioplasticity of the polyester resin (i) will be low, and the reduction in environmental impact will be insufficient.
[0105] The ester group concentration of the above-mentioned polyester resins (i) and (ii) is 2 mmol / g or more, preferably 2.5 to 10 mmol / g, more preferably 2.7 to 7 mmol / g, and particularly preferably 3 to 5 mmol / g. If the above-mentioned ester group concentration is too low, the polyester resin becomes softer, and its dent resistance and processability deteriorate.
[0106] As a method for adjusting the concentration of the ester group to a specified range, the following methods can be cited: selecting a polyol with 4 or fewer carbon atoms as the polyol component (b); increasing the content of a straight-chain carboxylic acid (a1) as the polycarboxylic acid (a); combining the two; etc.
[0107] The ester concentration (millomoles / g) mentioned above refers to the number of moles of ester bonds in 1g of polyester resin, which can be calculated, for example, from the amount added. The calculation method is to divide the mole count of the polycarboxylic acid (a) and polyol component (b) by the total weight of the finished product. An example of the calculation formula is shown below. It should be noted that the calculation method may need to be changed when using monomers containing both carboxylic acids and hydroxyl groups, or when polyesters are made from materials such as caprolactone.
[0108] <When polycarboxylic acids (a) are scarce>
[0109] Ester concentration (mmol / g) = [(A1 / a1×m1 + A2 / a2×m2 + A3 / a3×m3···) / Z] × 1000
[0110] A: Input amount (g) of polycarboxylic acids (a)
[0111] a: Molecular weight of polycarboxylic acids (a)
[0112] m: The number of carboxyl groups per molecule of polycarboxylic acids (a)
[0113] Z: Finished product weight (g)
[0114] <Case with low polyol content (b)>
[0115] Ester concentration (mmol / g) = [(B1 / b1×n1 + B2 / b2×n2 + B3 / b3×n3···) / Z] × 1000
[0116] B: Amount (g) of polyol component (b) added.
[0117] b: Molecular weight of polyol component (b)
[0118] n: The number of hydroxyl groups per molecule of polyol component (b)
[0119] Z: Finished product weight (g)
[0120] In addition, the above-mentioned ester group concentration can also be determined by known methods such as NMR.
[0121] In this invention, the bioplasticity of the polyester resin (i) is preferably 60% or more, more preferably 65% or more, further preferably 70% or more, and particularly preferably 80% or more. If the bioplasticity is low, the reduction in environmental impact tends to be insufficient.
[0122] Furthermore, the bioplasticity of the polyester resin (ii) is 60% or more, preferably 65% or more, further preferably 70% or more, and particularly preferably 80% or more. If the bioplasticity is low, the reduction in environmental impact becomes insufficient.
[0123] The upper limit of the bioplasticity is 100%. Furthermore, as a method to adjust the bioplasticity to the specified range, methods using plant-derived polycarboxylic acids and plant-derived polyols as the main components are recommended. In terms of effectively improving bioplasticity, it is particularly preferable to use plant-derived polycarboxylic acids (a).
[0124] Here, the bioplasticity of the aforementioned polyester resins (i) and (ii) refers to the ratio of the carbon composition of the plant-derived raw materials used in the manufacture of the aforementioned polyester resins (i) and (ii) to the total carbon of the polyester resins (i) and (ii), and the calculation method is as described below.
[0125] It should be noted that the bioplasticity of the above-mentioned polyester resins (i) and (ii) can be calculated based on the weighted average of the bioplasticity of polycarboxylic acids (a), polyols (b), and other components (such as compounds with carboxyl and hydroxyl groups in the molecule).
[0126] (Calculation method)
[0127] <Cases involving condensation polymerization>
[0128] Bioplasticity (%) = M1 / M2 × 100
[0129] In the formula, M1 is the number of moles of carbon in the plant-derived monomer when the molar ratio of the carboxyl group to the hydroxyl group is 1:1, calculated from the molar ratio of the input amounts of the polycarboxylic acid (a) and the polyol component (b), and M2 is the number of moles of carbon in all the constituent monomers.
[0130] <The case without condensation reaction>
[0131] Bioplasticity (%) = M3 / M2 × 100
[0132] In the formula, M3 is the number of moles of carbon input from plant-derived monomers, and M2 is the total number of moles of carbon constituting the monomers.
[0133] In addition, the aforementioned bioplasticity can also be determined by analyzing the composition ratio of the resin using NMR and calculating the carbon number of the plant-derived monomers / the total carbon number.
[0134] Furthermore, the aforementioned bioplasticity can also be determined according to the method of "ASTM D-6866" [Determination of the concentration of natural radioactive carbon (C-14)].
[0135] The heat of fusion of the polyester resins (i) and (ii), as measured by differential scanning calorimetry (DSC), is preferably 10 J / g or less, more preferably 5 J / g or less, even more preferably 2 J / g or less, and particularly preferably no heat of fusion is generated. If the heat of fusion is too high, crystallization may occur, resulting in poor storage stability of the resin solution, or a tendency for decreased stability and adhesive properties at low temperatures when forming adhesive sheets.
[0136] As a method for adjusting the heat of fusion of the above-mentioned crystals to a specified range, the following methods can be cited as examples: a method that uses polycarboxylic acids having alkyl groups in the side chain or polyols having alkyl groups in the side chain; a method that uses comonomers with 3 or more components, preferably 4 or more components; etc.
[0137] The heat of fusion of the crystal mentioned above refers to the energy consumed when heating and melting a crystallized substance, which can be measured using a differential scanning calorimeter (DSC).
[0138] The weight-average molecular weight of the aforementioned polyester resins (i) and (ii) is preferably 2,000 to 500,000, more preferably 10,000 to 300,000, and particularly preferably 50,000 to 150,000. If the weight-average molecular weight is too high, the workability decreases, and therefore, there is a tendency to require a large amount of solvent, resulting in a greater environmental impact. If the weight-average molecular weight is too low, there is a tendency to decrease the adhesive properties.
[0139] The weight-average molecular weights mentioned above are weight-average molecular weights calculated based on the standard polystyrene molecular weight. The high-performance liquid chromatography (HPLC) used (Tosoh Corporation, "HLC-8320GPC") employed a TSKgel SuperMultipore HZ-M column (size exclusion limit molecular weight: 2 × 10⁻⁶). 6 Theoretical plate number: 16,000 / plate; packing material: styrene-divinylbenzene copolymer; packing particle size: 4μm) 2 plates are connected in series for measurement.
[0140] In terms of preventing hydrolysis and improving durability, the acid value of the above-mentioned polyester resins (i) and (ii) is preferably 10 mg KOH / g or less, more preferably 5 mg KOH / g or less, particularly preferably 2 mg KOH / g or less, and especially preferably 1 mg KOH / g or less. If the acid value is too high, there is a tendency for the durability to decrease.
[0141] To adjust the acid value, one could increase the ratio of polyol component (b) during esterification or transesterification reactions, or adjust the reaction conditions. It should be noted that the lower limit of the acid value is typically 0 mg KOH / g.
[0142] The acid values of the above polyester resins (i) and (ii) were determined by neutralization titration based on JIS K0070.
[0143] It should be noted that the acid value in this invention refers to the content of carboxyl groups in polyester resins (i) and (ii). The aforementioned carboxyl groups also include those neutralized by alkaline compounds and those in a carboxylate ionic state.
[0144] The glass transition temperature (Tg) of the aforementioned polyester resins (i) and (ii) is preferably -90 to 20°C, particularly preferably -80 to 0°C, further preferably -60 to -20°C, and especially preferably -50 to -30°C. If the glass transition temperature (Tg) is too high, the adhesive composition tends to have reduced adhesion; if it is too low, the heat resistance or cohesive strength tends to decrease.
[0145] To adjust the glass transition temperature, for example, one could introduce an aromatic skeleton or change the alkyl chain length of the polycarboxylic acid component or the diol component.
[0146] The glass transition temperature (Tg) mentioned above was determined using a differential scanning calorimeter (DSCQ20) manufactured by TA Instruments Inc. It should be noted that the measurement temperature range was -90 to 100 °C, and the temperature rise rate was 10 °C / min.
[0147] The adhesive composition of the present invention preferably contains, for example, a hydrolysis inhibitor (iii), a crosslinking agent (iv), an urethane catalyst (v), an antioxidant (vi), and a tackifying resin (vii), together with the above-mentioned polyester resin (i) or (ii).
[0148] <Hydrolysis Inhibitor (iii)>
[0149] The aforementioned hydrolysis inhibitor (iii) is contained in order to ensure long-term durability.
[0150] As the aforementioned hydrolysis inhibitor (iii), conventionally known substances can be used, such as compounds that react with and bind to the carboxyl terminus of the aforementioned polyester resins (i) and (ii). Specifically, compounds containing functional groups such as carbodiimide, epoxy, and oxazoline groups can be used. Among these, compounds containing carbodiimide groups are preferred in terms of their high effectiveness in eliminating the catalytic activity of protons derived from the carboxyl terminus.
[0151] As the aforementioned carbodiimide-containing compounds, known carbodiimides having one or more carbodiimide groups (-N=C=N-) within the molecule are generally used. For further improving durability under high temperature and high humidity conditions, compounds containing two or more carbodiimide groups within the molecule, i.e., multi-carbodiimide compounds, are preferred; compounds containing three or more, five or more, and especially seven or more carbodiimide groups within the molecule are particularly preferred. It should be noted that the number of carbodiimide groups within the molecule is generally 50 or less. If there are too many carbodiimide groups, the molecular structure becomes excessively large, thus tending to reduce compatibility. Furthermore, high molecular weight polycarbodiimides generated by decarboxylation condensation of diisocyanates in the presence of a carbodiimide catalyst are also preferred.
[0152] Furthermore, regarding stability, it is preferable that the terminal isocyanate groups of the high molecular weight polycarbodiimide are capped by a capping agent. Examples of capping agents include compounds having active hydrogen that reacts with the isocyanate group, or compounds having an isocyanate group. Examples include monohydric alcohols, monocarboxylic acids, monoamines, and monoisocyanates having a substituent selected from carboxyl, amino, and isocyanate groups.
[0153] Examples of high molecular weight polycarbodiimides include those produced by decarboxylation condensation of the following diisocyanates.
[0154] Examples of the aforementioned diisocyanates include: 4,4'-diphenylmethane diisocyanate, 3,3'-dimethoxy-4,4'-diphenylmethane diisocyanate, 3,3'-dimethyl-4,4'-diphenylmethane diisocyanate, 4,4'-diphenyl ether diisocyanate, 3,3'-dimethyl-4,4'-diphenyl ether diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 1-methoxyphenyl-2,4-diisocyanate, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, tetramethylphenyl diisocyanate, etc., which can be used alone or in combination of two or more. The aforementioned high molecular weight polycarbodiimide can be synthesized from these diisocyanates, or commercially available products can be used.
[0155] Commercially available examples of the aforementioned carbodiimide-containing compounds include, for example, the CARBODILITE (registered trademark) series manufactured by Nisshinbo Chemical Inc., among which CARBODILITE (registered trademark) “V-01”, “V-02B”, “V-03”, “V-04K”, “V-04PF”, “V-05”, “V-07”, “V-09”, and “V-09GB” are preferred in terms of excellent compatibility with organic solvents.
[0156] As for the aforementioned epoxy-containing compounds, glycidyl ester compounds, glycidyl ether compounds, etc. are preferred.
[0157] Specific examples of the aforementioned glycidyl ester compounds include: glycidyl benzoate, glycidyl tert-butylbenzoate, glycidyl p-toluene, glycidyl cyclohexanecarboxylic acid, glycidyl nonanoate, glycidyl stearate, glycidyl laurate, glycidyl palmitate, glycidyl behenate, glycidyl tert-carbonate, glycidyl oleate, glycidyl linoleate, glycidyl linolenic acid, glycidyl behenate, glycidyl stearate, diglycidyl terephthalate, and isophthalic acid. Diglycidyl ester, diglycidyl phthalate, diglycidyl naphthalene dicarboxylate, diglycidyl methyl terephthalate, diglycidyl hexahydrophthalate, diglycidyl tetrahydrophthalate, diglycidyl cyclohexane dicarboxylate, diglycidyl adipic acid, diglycidyl succinate, diglycidyl sebacate, diglycidyl dodecanoate, diglycidyl octadecanoate, triglycidyl trimellitate, and tetraglycidyl pyromellitic acid, etc., can be used alone or in combination of two or more.
[0158] Specific examples of the aforementioned glycidyl ether compounds include: phenyl glycidyl ether, o-phenyl glycidyl ether, 1,4-bis(β,γ-epoxypropoxy)butane, 1,6-bis(β,γ-epoxypropoxy)hexane, 1,4-bis(β,γ-epoxypropoxy)benzene, 1-(β,γ-epoxypropoxy)-2-ethoxyethane, 1-(β,γ-epoxypropoxy)-2-benzyloxyethane, 2,2-bis-[p-(β,γ-epoxypropoxy)phenyl]propane, 2,2-bis-(4-hydroxyphenyl)propane, 2,2-bis-(4-hydroxyphenyl)methane, etc., obtained by reacting bisphenols with epichlorohydrin, etc., and these compounds can be used alone or in combination of two or more.
[0159] As for the aforementioned oxazoline-containing compounds, bisoxazoline compounds are preferred. Specifically, examples include: 2,2'-bis(2-oxazoline), 2,2'-bis(4-methyl-2-oxazoline), 2,2'-bis(4,4-dimethyl-2-oxazoline), 2,2'-bis(4-ethyl-2-oxazoline), 2,2'-bis(4,4'-diethyl-2-oxazoline), 2,2'-bis(4-propyl-2-oxazoline), 2,2'-bis(4-butyl-2-oxazoline), 2,2'-bis(4-ethyl ... 2,2'-hexyl-2-oxazoline, 2,2'-bis(4-phenyl-2-oxazoline), 2,2'-bis(4-cyclohexyl-2-oxazoline), 2,2'-bis(4-benzyl-2-oxazoline), 2,2'-p-phenylenebis(2-oxazoline), 2,2'-m-phenylenebis(2-oxazoline), 2,2'-o-phenylenebis(2-oxazoline), 2,2'-p-phenylenebis(4-methyl-2-oxazoline), 2,2'-p-phenylenebis(2-phenylene) Bis(4,4-dimethyl-2-oxazoline), 2,2'-m-phenylenebis(4-methyl-2-oxazoline), 2,2'-m-phenylenebis(4,4-dimethyl-2-oxazoline), 2,2'-ethylenebis(2-oxazoline), 2,2'-tetramethylenebis(2-oxazoline), 2,2'-hexamethylenebis(2-oxazoline), 2,2'-octamethylenebis(2-oxazoline), 2,2'-decamethylenebis(2-oxazoline) 2,2'-Ethylenebis(4-methyl-2-oxazoline), 2,2'-tetramethylenebis(4,4-dimethyl-2-oxazoline), 2,2'-9,9'-diphenoxyethanebis(2-oxazoline), 2,2'-cyclohexylenebis(2-oxazoline), 2,2'-diphenylenebis(2-oxazoline), etc., among which 2,2'-bis(2-oxazoline) is most preferred from the viewpoint of reactivity with polyester resins (i) and (ii). Furthermore, two or more of these resins can be used alone or in combination.
[0160] As the above-mentioned hydrolysis inhibitor (iii), it is preferred to use one with low volatility. Therefore, it is preferred to use one with a high number average molecular weight, typically 300 to 10,000, preferably 1,000 to 5,000.
[0161] Furthermore, from the viewpoint of hydrolysis resistance, a high weight-average molecular weight is preferred when using hydrolysis inhibitor (iii). The weight-average molecular weight of the hydrolysis inhibitor (iii) is preferably 500 or more, more preferably 2000 or more, and even more preferably 3000 or more. It should be noted that the upper limit of the weight-average molecular weight is typically 50,000.
[0162] If the molecular weight of the hydrolysis inhibitor (iii) is too small, its hydrolysis resistance tends to decrease. It should be noted that if the molecular weight is too large, its compatibility with polyester resins (i) and (ii) tends to decrease.
[0163] In the hydrolysis inhibitor (iii), compounds containing carbodiimide groups are preferably used, wherein the carbodiimide equivalent is preferably 50 to 10,000, particularly preferably 100 to 1,000, and even more preferably 150 to 500. It should be noted that the carbodiimide equivalent refers to the chemical weight of each carbodiimide group.
[0164] The content of the hydrolysis inhibitor (iii) is preferably 0.01 to 10 parts by weight, particularly preferably 0.1 to 5 parts by weight, and even more preferably 0.2 to 3 parts by weight relative to 100 parts by weight of the polyester resin (i) or (ii). If the content is too high, turbidity may occur due to poor compatibility with the polyester resin (i) or (ii); if the content is too low, sufficient durability may be difficult to obtain.
[0165] Furthermore, the content of the hydrolysis inhibitor (iii) is preferably optimized according to the acid value of the polyester resin (i) or (ii). The molar ratio of the total number of moles (y) of the functional groups of the hydrolysis inhibitor (iii) in the adhesive composition to the total number of moles (x) of the acidic functional groups of the polyester resin (i) or (ii) in the adhesive composition [(y) / (x)] is preferably 0.5 ≤ (y) / (x), particularly preferably 1 ≤ (y) / (x) ≤ 1000, and even more preferably 1.5 ≤ (y) / (x) ≤ 100.
[0166] If the molar ratio of (y) to (x) is too low, the resistance to damp heat tends to decrease. It should be noted that if the molar ratio of (y) to (x) is too high, the compatibility with polyester resins (i) or (ii) tends to decrease, or the adhesion, cohesion, and durability tend to decrease.
[0167] <Cross-linking agent (iv)>
[0168] The adhesive composition of the present invention preferably further contains a crosslinking agent (iv), which, by containing a crosslinking agent (iv), causes the polyester resin (i) or (ii) to be crosslinked with the crosslinking agent (iv), thereby improving its aggregation strength and performance as an adhesive.
[0169] Examples of crosslinking agents (iv) include polyisocyanate compounds and polyepoxy compounds, which have functional groups that react with at least one of the hydroxyl and carboxyl groups contained in the polyester resins (i) and (ii). Additionally, polyfunctional acrylic monomers and urethane acrylate oligomers that exhibit increased aggregation strength even without reacting with the polyester resins (i) and (ii) can also be used. Among these, polyisocyanate compounds are particularly preferred from the perspective of achieving a good balance between initial adhesion, mechanical strength, and heat resistance.
[0170] Examples of the aforementioned polyisocyanate compounds include: tetramethylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, phenyl dimethyl diisocyanate, hydrogenated phenyl dimethyl diisocyanate, tetramethylphenyl dimethyl diisocyanate, 1,5-naphthalene diisocyanate, triphenylmethane triisocyanate, and other polyisocyanates. Additionally, examples include: adducts of the aforementioned polyisocyanates with polyols such as trimethylolpropane, biuret forms of these polyisocyanate compounds, and isocyanurate forms. It should be noted that the aforementioned polyisocyanate compounds can also be formed by capping the isocyanate portion with phenol, lactam, or the like. These crosslinking agents (iv) can be used alone or in combination of two or more.
[0171] The content of the crosslinking agent (iv) can be appropriately selected according to the molecular weight of the polyester resins (i) and (ii) and the intended use. Generally, it is preferred that the crosslinking agent (iv) contains 0.2 to 10 equivalents of reactive groups relative to at least one of the hydroxyl and carboxyl groups contained in the polyester resins (i) or (ii), particularly preferably 0.5 to 5 equivalents, and even more preferably 0.5 to 3 equivalents. If the equivalent number of reactive groups contained in the crosslinking agent (iv) is too small, there is a tendency for reduced aggregation force; if it is too large, there is a tendency for reduced flexibility.
[0172] In addition, the content of the crosslinking agent (iv) is preferably 0.01 to 10 parts by weight, particularly preferably 0.1 to 8 parts by weight, further preferably 0.5 to 6 parts by weight, and especially preferably 1 to 4 parts by weight relative to 100 parts by weight of polyester resin (i) or (ii).
[0173] If the amount of the crosslinking agent is too small, the cohesive force tends to decrease; if the amount is too large, the flexibility tends to decrease and the required adhesive force cannot be obtained.
[0174] In addition, in the reaction of polyester resins (i) and (ii) with crosslinking agent (iv), organic solvents that do not have functional groups that react with these components (i), (ii) and (iv), such as esters like ethyl acetate and butyl acetate, ketones like methyl ethyl ketone and methyl isobutyl ketone, and aromatic organic solvents like toluene and xylene, can be used. They can be used alone or in combination of two or more.
[0175] <Aminoesterification catalyst (v)>
[0176] From the perspective of reaction rate, the adhesive composition of the present invention more preferably contains an urethane catalyst (v).
[0177] Examples of catalysts for amine esterification (v) include organometallic compounds and tertiary amine compounds. They can be used alone or in combination of two or more.
[0178] Examples of organometallic compounds include zirconium compounds, iron compounds, tin compounds, titanium compounds, lead compounds, cobalt compounds, and zinc compounds.
[0179] Examples of zirconium compounds include zirconium naphthenate and zirconium acetylacetonate.
[0180] Examples of iron-based compounds include iron acetylacetone and iron 2-ethylhexanoate.
[0181] Examples of tin-based compounds include dibutyltin dichloride, dibutyltin oxide, and dibutyltin dilaurate.
[0182] Examples of titanium-based compounds include dibutyl titanium dichloride, tetrabutyl titanate, and butoxy titanium trichloride.
[0183] Examples of lead compounds include lead oleate, lead 2-ethylhexanoate, lead benzoate, and lead naphthenate.
[0184] Examples of cobalt compounds include cobalt 2-ethylhexanoate and cobalt benzoate.
[0185] Examples of zinc compounds include zinc naphthenate and zinc 2-ethylhexanoate.
[0186] In addition, examples of the aforementioned tertiary amine compounds include triethylamine, triethylenediamine, and 1,8-diazabicyclo-(5,4,0)-undec-7-ene.
[0187] Among these amine esterification catalysts (v), organometallic compounds are preferred, and zirconium-based compounds are particularly preferred, in terms of reaction rate and pot life of the binder layer. Furthermore, the amine esterification catalyst (v) preferably incorporates acetylacetone as a catalytic inhibitor. The inclusion of acetylacetone is advantageous in suppressing catalytic activity at low temperatures and extending the pot life.
[0188] The content of the urethane catalyst (v) is preferably 0.0001 to 1 part by weight, particularly preferably 0.001 to 0.1 parts by weight, and even more preferably 0.01 to 0.05 parts by weight relative to 100 parts by weight of the polyester resin (i) or (ii). If the above content is too low, the curing time until the crosslinking reaction is completed tends to be longer; if it is too high, the adhesive properties tend to decrease.
[0189] <Antioxidants (vi)>
[0190] From the perspective of improving the stability of the resin, the adhesive composition of the present invention more preferably contains an antioxidant (vi).
[0191] Examples of antioxidants (vi) include hindered phenolic antioxidants, amine antioxidants, sulfur-based antioxidants, and phosphoric acid antioxidants. Among these, at least one selected from hindered phenolic antioxidants, amine antioxidants, and phosphoric acid antioxidants is preferred, and antioxidants formed from hindered phenolic compounds are particularly preferred.
[0192] As hindered phenolic antioxidants, examples include antioxidants with a hindered phenolic structure in which at least one of the carbon atoms adjacent to the carbon atom on the aromatic ring to which the hydroxyl group of phenol is bonded is a sterically hindered group such as tert-butyl.
[0193] The content of antioxidant (vi) relative to 100 parts by weight of polyester resin (i) or (ii) is preferably 0.01 to 10 parts by weight, more preferably 0.03 to 8 parts by weight, and even more preferably 0.05 to 5 parts by weight.
[0194] If the above content is too low, it tends to leave adhesive residue on the adhered objects; if it is too high, it tends to reduce the adhesive properties.
[0195] <Tackifying Resin (vii)>
[0196] In this invention, it is preferable to contain a tackifying resin (vii) in order to improve the adhesive properties.
[0197] The aforementioned tackifying resin (vii) is not particularly limited, and conventionally known substances can be used. Examples of the aforementioned tackifying resin (vii) include hydrocarbon-based tackifying resins, terpene-based resins, phenolic resins, rosin-based resins, xylene resins, epoxy resins, polyamide resins, ketone resins, and elastic resins. These can be used alone or in combination of two or more. Among these, hydrocarbon-based tackifying resins, terpene-based resins, and rosin-based resins are preferred for improving adhesive properties. Furthermore, regarding the stability of the adhesive, it is particularly preferred that the aforementioned tackifying resin (vii) contains at least one of a hydrocarbon-based tackifying resin and a terpene-based resin; and furthermore, terpene-based resins are particularly preferred for maintaining a high degree of bioplasticity and achieving a balance with physical properties. Its content is preferably 30% by weight or more, more preferably 50% by weight or more, and more preferably 70% by weight or more of the total tackifying resin.
[0198] Examples of hydrocarbon-based tackifying resins include, for example, aliphatic hydrocarbon resins, aromatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aliphatic / aromatic petroleum resins (such as styrene-olefin copolymers), aliphatic / alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone resins, and coumarone-indene resins. Additionally, commercially available products include, for example, "FTR6100," "FTR6110," and "FTR6125" manufactured by Mitsui Chemicals, Inc.
[0199] Examples of terpene-based resins include terpene resins, terpene phenolic resins, and aromatic modified terpene resins. Specifically, terpene-based resins obtained by modifying α-pinene polymers, β-pinene polymers, and dipentene polymers with phenols, aromatics, hydrogenation, or hydrocarbons can be used. Among these, terpene resins are preferred for their tendency to increase adhesion after 24 hours of adhesion, while terpene phenolic resins are preferred for their high adhesion to olefins. Commercially available products include, for example, "YS POLYSTAR S145," "YS RESIN PX1000," "YS RESIN PX1250," "YS POLYSTAR T145," "YS RESIN TO115," "YS POLYSTAR U130," and "CLEARON P125" manufactured by Yasuhara Chemical Co., Ltd.
[0200] Examples of phenolic resins that can be used include condensates of various phenols such as phenol, m-cresol, 3,5-xylenol, p-alkylphenol, and resorcinol with formaldehyde. Furthermore, cresol obtained by reacting the aforementioned phenols with formaldehyde in an alkaline catalyst; phenolic varnish obtained by reacting the aforementioned phenols with formaldehyde in an acid catalyst; and rosin-modified phenolic resin obtained by thermally polymerizing phenol with unmodified or modified rosin, its derivatives, or other rosin compounds in an acid catalyst.
[0201] Examples of rosin-based resins include rosin resin, polymerized rosin resin, hydrogenated rosin resin, rosin ester resin, hydrogenated rosin ester resin, rosin phenolic resin, and polymerized rosin ester. Specifically, unmodified rosins (raw rosin) such as rosin resin, wood rosin, and tall oil rosin can be used; modified rosins that have been hydrogenated, disproportionated, polymerized, or modified by other chemical methods; and their derivatives. Commercially available products include, for example, "HARITACK TF," "HARITACK 8LJA," "HARITACK PH," "HARITACK FK100," and "HARITACK PCJ" manufactured by Harima Chemicals Group, Inc.
[0202] The acid value of the tackifying resin (vii) is preferably 30 mg KOH / g or less, particularly preferably 10 mg KOH / g or less, further preferably 3 mg KOH / g or less, and especially preferably 1 mg KOH / g or less. When multiple tackifying resins are used in combination, it is preferable that their average value is within the above range.
[0203] The softening point of the tackifying resin (vii) (determined, for example, by the ring and ball method) is preferably 80–170°C, particularly preferably 85–160°C, and more preferably 95–150°C. A softening point within the above range can improve adhesive properties (adhesive strength, cohesive strength), which is preferable.
[0204] In this invention, in order to maintain a high degree of bioplasticity of the adhesive as a whole, the tackifying resin (vii) is preferably a plant-derived tackifying resin. Examples of plant-derived tackifying resins include terpene resins and rosin resins.
[0205] The content of the tackifying resin (vii) relative to 100 parts by weight of the aforementioned polyester resin (i) or (ii) is preferably 2 to 100 parts by weight, more preferably 5 to 80 parts by weight, further preferably 6 to 50 parts by weight, particularly preferably 8 to 30 parts by weight, and especially preferably 9 to 20 parts by weight. If the above content is too high, the adhesive layer tends to become excessively hard and the adhesion becomes easily reduced; if it is too low, the additive effect tends to be difficult to obtain.
[0206] In addition to the polyester resin (i) or (ii), hydrolysis inhibitor (iii), crosslinking agent (iv), urethane catalyst (v), antioxidant (vi), and tackifying resin (vii) mentioned above, the adhesive composition of the present invention may also contain additives such as softeners, ultraviolet absorbers, stabilizers, and antistatic agents, as well as inorganic or organic fillers, metal powders, pigments, and other powdered or granular additives, without impairing the effects of the present invention. Furthermore, it may contain small amounts of impurities contained in the raw materials used to manufacture the adhesive components.
[0207] They can be used individually or in combination of two or more.
[0208] Furthermore, the adhesive of the present invention is formed by crosslinking the above-described adhesive composition.
[0209] Furthermore, the bioplasticity of the adhesive of the present invention is preferably 60% or more, more preferably 65% or more, further preferably 70% or more, and particularly preferably 80% or more. The bioplasticity of the above-mentioned adhesive can be adjusted by adjusting the type and amount of polyester resin (i), (ii), and other compounding components.
[0210] The bioplasticity of the above-mentioned adhesive can be determined by taking into account the bioplasticity of the polyester resin obtained by the above method and the ratio of bio-derived carbon for each of the other components, and then calculating them by weighted average.
[0211] In addition, the bioplasticity of the above-mentioned adhesive can be determined by using the aforementioned NMR method, according to ASTM D-6866 [Determination of Natural Radiocarbon (C-14) Concentration].
[0212] Furthermore, the adhesive of the present invention is an adhesive obtained by crosslinking an adhesive composition, wherein the adhesive has an adhesive force (α) of 1 N / 25 mm or more under the following conditions, more preferably 5 to 100 N / 25 mm, further preferably 7 to 50 N / 25 mm, and particularly preferably 9 to 30 N / 25 mm. If the above adhesive force is too small, the bonding reliability will decrease.
[0213] Adhesive strength (α): When an adhesive sheet with an adhesive layer formed by an adhesive on a substrate is made, the 180-degree peel strength (N / 25mm) of the adherend after being placed on a SUS-BA board at 23°C and 50%RH for 30 minutes, at a peel speed of 300 mm / min.
[0214] Furthermore, the adhesive sheet of the present invention comprises an adhesive layer containing the above-mentioned adhesive, which is preferably formed on one or both sides of the supporting substrate.
[0215] It should be noted that in this invention, "sheet" also includes the meanings of "film" and "belt".
[0216] <Adhesive Sheet>
[0217] Adhesive sheets can be made, for example, as follows.
[0218] As a method for manufacturing the above-mentioned adhesive sheet, it can be manufactured according to a known general method for manufacturing adhesive sheets. For example, the above-mentioned adhesive composition is coated on a substrate and dried, a release sheet is attached to the adhesive composition layer on the opposite side, and the substrate is cured as needed to obtain the adhesive sheet of the present invention having an adhesive layer containing adhesive on the substrate.
[0219] Alternatively, by coating the above-mentioned adhesive composition onto the release sheet and drying it, then bonding the substrate to the adhesive composition layer on the opposite side and curing it as needed, the adhesive sheet of the present invention can also be obtained.
[0220] In addition, by forming an adhesive layer on the release sheet and then bonding the release sheet to the adhesive layer on the opposite side, a substrate-free double-sided adhesive sheet can be manufactured.
[0221] When using the obtained adhesive sheet or substrate-free double-sided adhesive sheet, the release sheet is peeled off from the adhesive layer to allow the adhesive layer to adhere to the object.
[0222] Examples of substrates include: polyester resins such as polyethylene naphthalate, polyethylene terephthalate, polybutylene terephthalate, and polyethylene terephthalate / ethylene isophthalate copolymer; polyolefin resins such as polyethylene, polypropylene, and polymethylpentene; polyvinyl fluoride resins such as polyvinylidene fluoride, polyvinylidene fluoride, and polyvinyl fluoride; polyamides such as nylon 6 and nylon 6,6; vinyl polymers such as polyvinyl chloride, polyvinyl chloride / vinyl acetate copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, polyvinyl alcohol, and vinylon; cellulose resins such as cellulose triacetate and cellophane; acrylic resins such as polymethyl methacrylate, polyethyl methacrylate, polyethyl acrylate, and polybutyl acrylate; sheets formed from synthetic resins such as polystyrene, polycarbonate, polyacrylate, polyimide, and cycloolefin polymers; metal foils made of aluminum, copper, and iron; papers such as high-quality paper and cellophane; and fabrics and nonwovens formed from glass fibers, natural fibers, and synthetic fibers. These substrates can be used as single-layer bodies or as multilayer bodies with two or more layers stacked together.
[0223] Of particular preference are substrates formed from polyethylene terephthalate and polyimide, especially polyethylene terephthalate, which has excellent adhesion to adhesives.
[0224] Furthermore, foam sheets containing foamed materials such as polyurethane foam, polyethylene foam, and polyacrylate foam can be used as the aforementioned substrate. Among these, polyethylene foam and polyacrylate foam are preferred from the perspectives of excellent conformability to the adhered object and excellent uniformity of adhesive strength.
[0225] The thickness of the aforementioned substrate is preferably 1 to 1000 μm, particularly preferably 2 to 500 μm, and even more preferably 3 to 300 μm.
[0226] As the aforementioned release sheet, for example, sheets, papers, cloths, non-woven fabrics, etc., formed from various synthetic resins exemplified in the above-described substrates can be used after a release treatment. Silicone-based release sheets are preferred.
[0227] As a coating method for the above-mentioned adhesive composition, for example, gravure roller coating machine, reverse roller coating machine, roller coating machine, dip roller coating machine, bar coating machine, doctor blade coating machine, spraying machine, comma coating machine, etc. can be used.
[0228] As for the above-mentioned curing conditions, the temperature is usually room temperature (23°C) to 70°C, and the time is usually 1 to 30 days. Specifically, for example, it can be carried out at 23°C for 1 to 20 days, preferably at 23°C for 3 to 14 days, or at 40°C for 1 to 10 days.
[0229] In addition, as drying conditions, the drying temperature is preferably 60-140°C, particularly preferably 80-120°C, and the drying time is preferably 0.5-30 minutes, particularly preferably 1-5 minutes.
[0230] The thickness of the adhesive layer in the aforementioned adhesive sheet and substrate-free double-sided adhesive sheet is preferably 2–500 μm, particularly preferably 5–200 μm, and even more preferably 10–100 μm. If the thickness of the adhesive layer is too thin, the adhesion tends to decrease; if it is too thick, it tends to be difficult to coat evenly and prone to problems such as air bubbles entering the coating film. It should be noted that, considering impact absorption, a thickness of 50 μm or more is preferred.
[0231] It should be noted that the thickness of the adhesive layer is calculated as follows: using an "ID-C112B" manufactured by Mitutoyo Corporation, the thickness of the constituent components other than the adhesive layer is subtracted from the measured thickness of the overall adhesive sheet.
[0232] Regarding the gelation rate of the adhesive layer in the aforementioned adhesive sheet, from the perspective of durability and adhesion, it is preferably 10% by weight or more, particularly preferably 20-80% by weight, further preferably 25-70% by weight, and especially preferably 27-45% by weight. If the gelation rate is too low, there is a tendency for reduced cohesive strength and reduced holding strength. It should be noted that if the gelation rate is too high, there is a tendency for increased cohesive strength and decreased adhesion strength.
[0233] The aforementioned gelation rate becomes the standard for the degree of crosslinking, and therefore, it is calculated, for example, by the following method: An adhesive sheet (without a release liner) formed by forming an adhesive layer on a polymer sheet (e.g., PET film) serving as the substrate is covered with a 200-mesh SUS wire mesh and immersed in toluene at 23°C for 24 hours. The weight percentage of the undissolved adhesive component remaining in the wire mesh after immersion relative to the weight of the adhesive component before immersion is taken as the gelation rate. The weight of the substrate is subtracted beforehand.
[0234] Furthermore, a release sheet can be provided on the outside of the adhesive layer for protection as needed. Additionally, since the adhesive layer is formed in an adhesive sheet on one side of the substrate, a peeling treatment is performed on the side of the substrate opposite to the adhesive layer, thereby protecting the adhesive layer using this peeling treatment surface.
[0235] The adhesive of the present invention can be used for bonding various components, especially for single-sided or double-sided adhesive sheets used for bonding optical components, for fixing components of portable electronic devices, and for fixing single-sided or double-sided adhesive sheets for fixing electronic components.
[0236] Example
[0237] The present invention will be further described below with reference to specific embodiments, but the present invention is not limited to the following embodiments as long as it does not deviate from its spirit. It should be noted that "parts" and "%" in the examples refer to weight.
[0238] In addition, the determination of the bioplasticity, ester concentration, heat of melting, weight-average molecular weight, glass transition temperature, acid value, and gelation rate of the polyester resin in the following examples was performed according to the aforementioned method.
[0239] Polyester resins are manufactured according to the following method.
[0240] [Manufacturing Example 1: Manufacturing of Polyester Resin (i-1)]
[0241] In a reactor equipped with a thermometer, stirrer, distillation column, nitrogen inlet pipe, and vacuum device, 17.8 parts (0.45 mol) of sebacic acid (as a polycarboxylic acid, a) and 61.4 parts (0.55 mol) of hydrogenated distilled dimer acid (manufactured by Croda International Plc, "PRIPOL 1009") were added; 20.7 parts (1.7 mol) of ethylene glycol (as a polyol, a) and 0.2 parts (0.0065 mol) of trimethylolpropane were added; and 0.01 parts of tetrabutyl titanate was added as a catalyst. The temperature was slowly increased to an internal temperature of 250°C, and the esterification reaction was carried out for 4 hours. Afterward, the internal temperature was increased to 260°C, and 0.01 parts of tetrabutyl titanate as a catalyst were added. The pressure was reduced to 1.33 hPa, and the polymerization reaction was carried out for 3 hours to produce a polyester resin (i-1).
[0242] The obtained polyester resin (i-1) has a bioplasticity of 92%, an ester concentration of 4.64 mmol / g, a heat of fusion of 0 J / g, a weight-average molecular weight of 58,000, a glass transition temperature (Tg) of -50℃, and an acid value of 0.4 mg KOH / g.
[0243] It should be noted that the plant-derived raw materials used in manufacturing Example 1 are sebacic acid and hydrogenated distilled dimer acid, with a content of 86% relative to the polyester resin (i-1).
[0244] [Manufacturing Example 2: Manufacturing of Polyester Resin (i-2)]
[0245] In a reactor equipped with a thermometer, stirrer, distillation column, nitrogen inlet pipe, and vacuum device, 84.3 parts (1.00 mol) of hydrogenated distilled dimer acid (manufactured by Croda International Plc, "PRIPOL 1009") as a polycarboxylic acid (a), 15.6 parts (1.7 mol) of ethylene glycol as a polyol component (b), 0.1 parts (0.0065 mol) of trimethylolpropane, and 0.01 parts of tetrabutyl titanate as a catalyst were added. The temperature was slowly increased to an internal temperature of 250°C, and the esterification reaction was carried out for 4 hours. Afterward, the internal temperature was increased to 260°C, 0.01 parts of tetrabutyl titanate as a catalyst were added, the pressure was reduced to 1.33 hPa, and the polymerization reaction was carried out for 3 hours to produce a polyester resin (i-2).
[0246] The obtained polyester resin (i-2) has a bioplasticity of 95%, an ester concentration of 3.36 mmol / g, a heat of fusion of 0 J / g, a weight-average molecular weight of 72,000, a glass transition temperature (Tg) of -47℃, and an acid value of 0.3 mg KOH / g.
[0247] It should be noted that the plant-derived raw material used in manufacturing Example 2 is hydrogenated distilled dimer acid, which accounts for 90% of the content of polyester resin (i-2).
[0248] [Manufacturing Example 3: Manufacturing of Polyester Resin (i-3)]
[0249] In a reactor equipped with a thermometer, stirrer, distillation column, nitrogen inlet pipe, and vacuum device, 80.6 parts (1.00 mol) of hydrogenated distilled dimer acid (manufactured by Croda International Plc, "PRIPOL 1009") as a polycarboxylic acid (a), 19.1 parts (1.5 mol) of 1,4-butanediol as a polyol component (b), 0.3 parts (0.015 mol) of trimethylolpropane, and 0.01 parts of tetrabutyl titanate as a catalyst were added. The temperature was slowly increased to an internal temperature of 250°C, and the esterification reaction was carried out for 4 hours. Afterward, the internal temperature was increased to 260°C, 0.01 parts of tetrabutyl titanate as a catalyst were added, the pressure was reduced to 1.33 hPa, and the polymerization reaction was carried out for 3 hours to produce a polyester resin (i-3).
[0250] The obtained polyester resin (i-3) has a bioplasticity of 86%, an ester concentration of 3.21 mmol / g, a heat of fusion of 0 J / g, a weight-average molecular weight of 71,000, a glass transition temperature (Tg) of -52℃, and an acid value of 0.3 mg KOH / g.
[0251] It should be noted that the plant-derived raw material used in manufacturing Example 3 is hydrogenated distilled dimer acid, which accounts for 86% of the content of polyester resin (i-3).
[0252] [Manufacturing Example 4: Manufacturing of Polyester Resin (i-4)]
[0253] In a reactor equipped with a thermometer, stirrer, distillation column, nitrogen inlet pipe, and vacuum device, 80.3 parts (1.00 mol) of hydrogenated distilled dimer acid (manufactured by Croda International Plc, "PRIPOL 1009") as a polycarboxylic acid (a), 7.9 parts (0.90 mol) of ethylene glycol, 11.7 parts (0.80 mol) of neopentyl glycol, and 0.1 parts (0.0065 mol) of trimethylolpropane, and 0.01 parts of tetrabutyl titanate as a catalyst were added. The temperature was slowly increased to an internal temperature of 250°C, and the esterification reaction was carried out for 4 hours. Afterward, the internal temperature was increased to 260°C, 0.01 parts of tetrabutyl titanate as a catalyst were added, the pressure was reduced to 1.33 hPa, and the polymerization reaction was carried out for 3 hours to produce a polyester resin (i-4).
[0254] The obtained polyester resin (i-4) has a bioplasticity of 91%, an ester concentration of 3.25 mmol / g, a heat of fusion of 0 J / g, a weight-average molecular weight of 72,000, a glass transition temperature (Tg) of -47℃, and an acid value of 0.2 mg KOH / g.
[0255] It should be noted that the plant-derived raw material used in manufacturing Example 4 is hydrogenated distilled dimer acid, which accounts for 87% of the content of polyester resin (i-4).
[0256] [Manufacturing Example 5: Manufacturing of Polyester Resin (i-5)]
[0257] In a reactor equipped with a thermometer, stirrer, distillation column, nitrogen inlet pipe, and vacuum device, 17.0 parts (0.45 mol) of sebacic acid (as a polycarboxylic acid, a) and 58.5 parts (0.55 mol) of hydrogenated distilled dimer acid (manufactured by Croda International Plc, "PRIPOL 1009") were added; 24.3 parts (2.1 mol) of ethylene glycol (as a polyol, a) and 0.2 parts (0.0065 mol) of trimethylolpropane were added; and 0.01 parts of tetrabutyl titanate was added as a catalyst. The temperature was slowly increased to an internal temperature of 250°C, and the esterification reaction was carried out for 4 hours. Afterward, the internal temperature was increased to 260°C, and 0.01 parts of tetrabutyl titanate as a catalyst were added. The pressure was reduced to 1.33 hPa, and the polymerization reaction was carried out for 3 hours to produce a polyester resin (i-5).
[0258] The obtained polyester resin (i-5) has a bioplasticity of 92%, an ester concentration of 4.64 mmol / g, a heat of fusion of 0 J / g, a weight-average molecular weight of 97,000, a glass transition temperature (Tg) of -50℃, and an acid value of 0.1 mg KOH / g.
[0259] It should be noted that the plant-derived raw materials used in manufacturing Example 5 are sebacic acid and hydrogenated distilled dimer acid, with a content of 86% relative to the polyester resin (i-5).
[0260] [Manufacturing Example 6: Manufacturing of Polyester Resin (i-6)]
[0261] In a reactor equipped with a thermometer, stirrer, distillation column, nitrogen inlet pipe, and vacuum device, 84.3 parts (1.00 mol) of hydrogenated distilled dimer acid (manufactured by Croda International Plc, "PRIPOL 1009") as a polycarboxylic acid (a), 15.6 parts (1.7 mol) of ethylene glycol as a polyol component (b), 0.1 parts (0.0065 mol) of trimethylolpropane, and 0.01 parts of tetrabutyl titanate as a catalyst were added. The temperature was slowly increased to an internal temperature of 250°C, and the esterification reaction was carried out for 4 hours. Afterward, the internal temperature was increased to 260°C, 0.01 parts of tetrabutyl titanate as a catalyst were added, the pressure was reduced to 1.33 hPa, and the polymerization reaction was carried out for 3 hours to produce a polyester resin (i-6).
[0262] The obtained polyester resin (i-6) has a bioplasticity of 95%, an ester concentration of 3.36 mmol / g, a heat of fusion of 0 J / g, a weight-average molecular weight of 88,000, a glass transition temperature (Tg) of -47℃, and an acid value of 0.1 mg KOH / g.
[0263] It should be noted that the plant-derived raw material used in manufacturing Example 6 is hydrogenated distilled dimer acid, which accounts for 90% of the content of polyester resin (i-6).
[0264] [Comparative Manufacturing Example 1: Manufacturing of Polyester Resin (i'-1)]
[0265] In a reactor equipped with a thermometer, stirrer, distillation column, nitrogen inlet pipe, and vacuum device, 49.2 parts (1.00 mol) of hydrogenated distilled dimer acid (manufactured by Croda International Plc, "PRIPOL 1009") as a polycarboxylic acid (a), 50.8 parts (1.09 mol) of dimer diol (manufactured by Croda International Plc, "PRIPOL 2033") as a polyol component (b), and 0.01 parts of tetrabutyl titanate as a catalyst were added. The temperature was slowly raised to an internal temperature of 200°C, and the esterification reaction was carried out for 4 hours. Afterward, the internal temperature was raised to 240°C, and 0.01 parts of tetrabutyl titanate as a catalyst were added. The pressure was reduced to 1.33 hPa, and the polymerization reaction was carried out for 3 hours to produce a polyester resin (i'-1).
[0266] The obtained polyester resin (i'-1) has a bioplasticity of 100%, an ester concentration of 1.78 mmol / g, a heat of fusion of 0 J / g, a weight-average molecular weight of 33000, a glass transition temperature (Tg) of -50℃, and an acid value of 0.1 mg KOH / g.
[0267] It should be noted that the plant-derived raw materials of Comparative Manufacturing Example 1 are hydrogenated distilled dimer acid and dimer diol, with a content of 100% relative to polyester resin (i'-1).
[0268] [Comparative Manufacturing Example 2: Manufacturing of Polyester Resin (i'-2)]
[0269] In a reactor equipped with a heating device, thermometer, stirrer, distillation column, nitrogen inlet pipe, and vacuum device, 9.6 parts (0.2 mol) of isophthalic acid and 46.8 parts (0.8 mol) of sebacic acid (as polycarboxylic acid, a) were added; 27.1 parts (0.900 mol) of neopentyl glycol, 13.0 parts (0.500 mol) of 1,4-butanediol, 3.0 parts (0.087 mol) of 1,6-hexanediol, and 0.5 parts (0.013 mol) of trimethylolpropane (tHMOP) were added; and 0.01 parts of tetrabutyl titanate was added as a catalyst. The temperature was slowly increased to an internal temperature of 250°C, and the esterification reaction was carried out for 4 hours. Afterward, the internal temperature was increased to 260°C, and 0.01 parts of tetrabutyl titanate as a catalyst were added. The pressure was reduced to 1.33 hPa, and the polymerization reaction was carried out for 3 hours to produce a polyester resin (i'-2).
[0270] The obtained polyester resin (i'-2) has a bioplasticity of 56%, an ester concentration of 7.7 mmol / g, a heat of fusion of 0 J / g, a weight-average molecular weight of 80,000, a glass transition temperature (Tg) of -49℃, and an acid value of 0.4 mg KOH / g.
[0271] It should be noted that the plant-derived raw material in Comparative Manufacturing Example 2 is sebacic acid, and its content relative to polyester resin (i'-2) is 52%.
[0272] [Comparative Manufacturing Example 3: Manufacturing of Polyester Resin (i'-3)]
[0273] In a reactor equipped with a thermometer, stirrer, distillation column, nitrogen inlet pipe, and vacuum device, 17.8 parts (0.45 mol) of sebacic acid (as a polycarboxylic acid), 61.2 parts (0.55 mol) of hydrogenated distilled dimer acid (manufactured by Croda International Plc, "PRIPOL 1006"), 20.6 parts (1.387 mol) of 1,3-propanediol (as a polyol component (b), and 0.3 parts (0.013 mol) of trimethylolpropane, and 0.01 parts of tetrabutyl titanate as a catalyst were added. The temperature was slowly increased to an internal temperature of 250°C, and the esterification reaction was carried out for 4 hours. Afterward, the internal temperature was increased to 260°C, 0.01 parts of tetrabutyl titanate as a catalyst were added, the pressure was reduced to 1.33 hPa, and the polymerization reaction was carried out for 3 hours to produce a polyester resin (i'-3).
[0274] The obtained polyester resin (i'-3) has a bioplasticity of 100%, an ester concentration of 4.49 mmol / g, a heat of fusion of 0 J / g, a weight-average molecular weight of 112000, a glass transition temperature (Tg) of -56℃, and an acid value of 0.5 mg KOH / g.
[0275] It should be noted that the plant-derived raw materials of Comparative Manufacturing Example 3 are hydrogenated distilled dimer acid, sebacic acid, and 1,3-propanediol, and the content of hydrogenated distilled dimer acid and sebacic acid in the polyester resin (i'-3) is 83%.
[0276] [Comparative Manufacturing Example 4: Manufacturing of Polyester Resin (i'-4)]
[0277] In a reactor equipped with a thermometer, stirrer, distillation column, nitrogen inlet pipe, and vacuum device, 84.1 parts (1.00 mol) of hydrogenated distilled dimer acid (manufactured by Croda International Plc, "PRIPOL 1006") as a polycarboxylic acid (a), 15.6 parts (1.387 mol) of 1,3-propanediol as a polyol component (b), 0.3 parts (0.013 mol) of trimethylolpropane, and 0.01 parts of tetrabutyl titanate as a catalyst were added. The temperature was slowly increased to an internal temperature of 250°C, and the esterification reaction was carried out for 4 hours. Afterward, the internal temperature was increased to 260°C, and 0.01 parts of tetrabutyl titanate as a catalyst were added. The pressure was reduced to 1.33 hPa, and the polymerization reaction was carried out for 3 hours to produce a polyester resin (i'-4).
[0278] The obtained polyester resin (i'-4) has a bioplasticity of 100%, an ester concentration of 3.28 mmol / g, a heat of fusion of 0 J / g, a weight-average molecular weight of 157,000, a glass transition temperature (Tg) of -52℃, and an acid value of 0.8 mg KOH / g.
[0279] It should be noted that the plant-derived raw materials of Comparative Manufacturing Example 4 are hydrogenated distilled dimer acid and 1,3-propanediol, and the content of hydrogenated distilled dimer acid in the polyester resin (i'-4) is 88%.
[0280] The composition and properties of each polyester resin manufactured in the above manufacturing examples are shown in Tables 1 and 2 below.
[0281] [Table 1]
[0282]
[0283] [Table 2]
[0284]
[0285] For the polyester resin manufactured in the above manufacturing example, the bioplasticity, ester concentration, and heat of melting of the crystal were confirmed. The results showed that (i-1) to (i-6) all met the ranges defined in this invention, and it can be used as a polyester resin (i) or (ii) for the adhesive composition of this invention.
[0286] On the other hand, the bioplasticity of polyester resins (i'-2), which are commonly used as adhesives, is about 56%, which is insufficient to reduce the environmental impact.
[0287] Next, the components were prepared as follows before preparing the adhesive composition.
[0288] [Hydrolysis inhibitor (iii)]
[0289] • Carbodiimide compounds (iii-1): “CARBODILITE V-09GB” (manufactured by Nisshinbo Chemical Inc.)
[0290] [Cross-linking agent (iv)]
[0291] • Isocyanate-based crosslinking agent (iv-1): "CORONATE HX" (manufactured by Tosoh Corporation)
[0292] • Isocyanate-based crosslinking agent (iv-2): "CORONATE L" (manufactured by Tosoh Corporation)
[0293] [Aminated catalyst (v)]
[0294] • Zirconium compounds (v-1): “ORGATIX ZC-150” (manufactured by Matsumoto Fine Chemical Co., Ltd.) (diluted with acetylacetone to a solid content concentration of 1%)
[0295] [Antioxidants (vi)]
[0296] • Hindered phenolic antioxidant (VI-1): “IRGANOX1010” (manufactured by BASF SE)
[0297] [Tackifying resin (vii)]
[0298] • Aromatic hydrocarbon resin (vii-1): "FTR6100" (manufactured by Mitsui Chemicals, Inc.) (softening point: 95℃, acid value: less than 0.1 mg KOH / g) Bioplasticity: 0%
[0299] • Polymeric rosin ester (vii-2): "HARITACK PCJ" (manufactured by Harima Chemicals Group, Inc.) (softening point: 118–128℃, acid value: below 16 mg KOH / g) Bioplasticity: 88%
[0300] • Special Rosin Ester (vii-3): “SUPERESTER A-100” (manufactured by Arakawa Chemical Industries, Ltd.) (Softening point: 100℃, acid value: below 10mgKOH / g) Bioplasticity: 99%
[0301] • Aromatic terpenes (vii-4): “YS RESIN TO115” (manufactured by Yasuhara Chemical Co., Ltd.) (softening point: 115℃, acid value: 0 mg KOH / g) Bioplasticity: ≥70%
[0302] • Terpene resin (vii-5): “YS RESIN PX1000” (manufactured by Yasuhara Chemical Co., Ltd.) (softening point: 110℃, acid value: 0mgKOH / g) Bioplasticity: ≥90%
[0303] Next, using the polyester resins (i-1 to i-6 and i'-1 to i'-4) obtained above, adhesive compositions were prepared as described in the following examples and comparative examples, and adhesive sheets were made.
[0304] [Example 1]
[0305] The polyester resin (i-1) obtained above was diluted with ethyl acetate to a solids concentration of 50%. Relative to 100 parts of this solids, 1 part of carbodiimide compound (iii-1) (solids), 2 parts of isocyanate crosslinking agent (iv-2), 0.02 parts of zirconium compound (v-1) (solids), and 0.1 parts of hindered phenolic antioxidant (vi-1) were mixed and stirred to obtain an adhesive composition.
[0306] The obtained adhesive composition was coated onto a polyethylene terephthalate (PET) film (38 μm thick) to a dried thickness of approximately 25 μm, and then dried at 100°C for 3 minutes to form an adhesive layer. Subsequently, a release-treated PET film (release film) was attached to the adhesive layer to protect its surface, and the film was cured at 40°C for 10 days to obtain an adhesive sheet.
[0307] [Examples 2-14, Comparative Examples 1-7]
[0308] In Example 1, the adhesive composition was prepared according to Table 3 below, except that the preparation was carried out in the same manner to obtain an adhesive sheet.
[0309] [Table 3]
[0310]
[0311] * Blending amount (parts) relative to 100 parts of the solid component of the polyester resin.
[0312] The adhesive sheets obtained in Examples 1-14 and Comparative Examples 1-7 were evaluated as follows. The evaluation results are shown in Table 4 below.
[0313] <Adhesive strength (peel strength) (for SUS-BA)>
[0314] Prepare a SUS-BA board as the substrate. Cut the adhesive sheet obtained above into 25mm × 200mm pieces at 23°C and 50% RH to obtain test samples. Peel the release film from the test sample, allowing the adhesive layer side of the test sample to abut against the SUS-BA board. Apply pressure with a 2kg roller repeatedly on the test sample. Then, allow the test sample to stand for 30 minutes under the same atmosphere. Measure the 180-degree peel strength (N / 25mm) using an Autograph (manufactured by Shimadzu Corporation, AUTOGRAPH AGS-H500N) at a peel speed of 300mm / min, and evaluate it according to the following criteria.
[0315] (Evaluation Criteria)
[0316] ◎···5N / 25mm or more.
[0317] ○··· 1N / 25mm or more but less than 5N / 25mm.
[0318] ×··· Less than 1N / 25mm.
[0319] <Adhesive strength after 24 hours (peel strength after 24 hours)>
[0320] Prepare a SUS-BA board as the substrate. Cut the adhesive sheet obtained above into 25mm × 200mm pieces at 23°C and 50% RH to obtain test samples. Peel the release film from the test sample, allowing the adhesive layer side of the test sample to abut against the SUS-BA board. Apply pressure with a 2kg roller repeatedly on the test sample. Then, allow the test sample to stand for 24 hours in the same atmosphere. Measure the 180-degree peel strength (N / 25mm) using an Autograph (manufactured by Shimadzu Corporation, AUTOGRAPH AGS-H500N) at a peel speed of 300mm / min, and evaluate it according to the following criteria.
[0321] (Evaluation Criteria)
[0322] ◎···20N / 25mm or more.
[0323] ○··· 13N / 25mm or more and less than 20N / 25mm.
[0324] ×··· Less than 13N / 25mm.
[0325] <Adhesion (peel strength) (for PP)>
[0326] Prepare a polypropylene (PP) sheet (manufactured by Nippon Testpanel Co., Ltd., PP 2.0×70×150mm) as the adhesive. Cut the adhesive sheet obtained above into 25mm×200mm pieces at 23°C and 50% RH to obtain test samples. Peel the release film from the test sample, so that the adhesive layer side of the test sample abuts against the PP sheet. Apply pressure by repeatedly pressing a 2kg roller onto the test sample. Then, allow the obtained test samples to stand for 30 minutes under the same atmosphere. Measure the 180° peel strength (N / 25mm) using an Autograph (manufactured by Shimadzu Corporation, AUTOGRAPH AGS-H 500N) at a peel speed of 300mm / min, and evaluate it according to the following criteria.
[0327] (Evaluation Criteria)
[0328] ◎···10N / 25mm or more.
[0329] ○···6N / 25mm or more and less than 10N / 25mm.
[0330] ×··· Less than 6N / 25mm.
[0331] <Retention Force (Cohesion)>
[0332] For the adhesive sheet obtained above, according to JIS Z-0237, SUS304 is used as the adhesive material. After adhesion with an adhesion area of 25mm×25mm, it is left to stand at 80°C for 20 minutes. A load of 1kg is applied to the obtained material. For the case where it does not fall off even after 24 hours of standing, the deviation after 24 hours is measured and evaluated according to the following criteria.
[0333] (Evaluation Criteria)
[0334] Even after being left to stand for 24 hours, it did not fall off.
[0335] ×···Falls during the 24-hour resting period.
[0336] <Dent Resistance>
[0337] The adhesive composition described above was applied to a polyethylene terephthalate (PET) film (38 μm thick) as the substrate to a dried thickness of approximately 25 μm, and then dried at 100°C for 3 minutes to form an adhesive layer. Subsequently, a PET film that had undergone a release treatment (release film) was attached to the adhesive layer. A 2 kg roller was placed on the release film, and after a 10-second pause, the adhesive layer was visually observed and evaluated according to the following criteria.
[0338] (Evaluation Criteria)
[0339] ○···No change.
[0340] ×···There are residual dents indicating that a roller was placed there.
[0341] <Processability>
[0342] The adhesion of the adhesive to the blade of the cutter when the adhesive sheet obtained above is cut into 25mm wide pieces is visually observed, and evaluated according to the following criteria.
[0343] (Evaluation Criteria)
[0344] ○···No adhesive was applied to the blade.
[0345] ×··· There is glue attached to the blade.
[0346] <Transparency>
[0347] The release film is peeled off from the adhesive layer of the adhesive sheet obtained above, and the exposed adhesive layer is then bonded to an alkali-free glass plate (manufactured by Corning Inc., EAGLE XG) to produce a test piece with a PET film / adhesive layer / alkali-free glass plate composition.
[0348] For this test sheet, the haze was measured using a HAZE MATER NDH2000 (manufactured by Nippon Denshoku Industries Co., Ltd.). The haze value of the adhesive sheet was obtained by subtracting the haze value of the PET film, and the evaluation was based on the following criteria. It should be noted that the haze meter was based on JIS K7361-1.
[0349] ○···The fog level is below 3.
[0350] △···The fog level is between 3 and 10.
[0351] ×···The fog level exceeds 10.
[0352] [Table 4]
[0353]
[0354] According to the results in Table 4, the adhesive sheets of Examples 1-14 not only exhibit desirable adhesive properties to metal substrates but also to substrates that are difficult to bond, such as polyolefin resins, demonstrating excellent balance between adhesive strength and holding power. Furthermore, the adhesive sheets of Examples 1-14 exhibit excellent dent resistance when manufactured in a narrower format, excellent processability as adhesive sheets, and excellent processability and transparency during lamination. By also containing tackifying resins, they possess even better adhesive properties and, consequently, long-lasting adhesive properties.
[0355] In contrast, the adhesives of Comparative Examples 1-3, which used conventional polyester resins with high bioplasticity, did not meet the requirements for adhesive properties. Furthermore, the adhesive layers formed using the adhesives of Comparative Examples 1-3 were excessively soft, resulting in dents, or exhibited poor processability and transparency. Moreover, the adhesives of Comparative Examples 1 and 3-7, which used polyester resins that did not use diols with an even number of carbon atoms as polyol components, showed insufficient adhesion to polyolefin resins, or poor balance between adhesion and holding power.
[0356] The above embodiments illustrate specific aspects of the present invention, but these embodiments are merely examples and not intended to be limiting. Various modifications that will be apparent to those skilled in the art are within the scope of this invention.
[0357] Industrial availability
[0358] The adhesive of the present invention uses plant-derived raw materials that are environmentally friendly. When using polyester resin with high bioplasticity, it has good adhesion to various adhered objects such as metals and plastics. When it is made into smaller pieces, it also has excellent processability, dent resistance and transparency. It is used as a single-sided or double-sided adhesive sheet for bonding optical components, for fixing components of portable electronic devices, and for fixing electronic components.
Claims
1. An adhesive obtained by crosslinking an adhesive composition, said adhesive composition comprising a polyester resin (i), said polyester resin (i) having structural sites derived from a polycarboxylic acid (a) and structural sites derived from a polyol component (b). The polyester resin (i) contains at least 60% by weight of structural sites derived from at least one of the group consisting of dimer acids, sebacic acids, and dimer diols, relative to the polyester resin (i). A diol (b1) containing an even number of carbon atoms is used as the polyol component (b), wherein, Excluding dimer diols, The polyester resin (i) has an ester group concentration of 2 mmol / g or higher, an acid value of 10 mg / KOH or lower, and a weight-average molecular weight greater than 50,000 and less than 500,000. The adhesive force (α) is 1 N / 25 mm or more under the following conditions. Adhesive strength (α): When an adhesive sheet with an adhesive layer formed by an adhesive on a substrate is made, the 180-degree peel strength of the adherend to the SUS-BA board after standing for 30 minutes at 23°C and 50%RH, at a peel speed of 300 mm / min, is expressed in N / 25 mm.
2. The adhesive according to claim 1, wherein, The diol with an even number of carbon atoms (b1) is an aliphatic diol with a straight-chain structure.
3. The adhesive according to claim 1 or 2, wherein, The polycarboxylic acid class (a) contains less than 70 mol% of a straight-chain carboxylic acid class (a1).
4. The adhesive according to claim 1 or 2, wherein, The polyol component (b) contains 10 to 100 mol% of a diol (b1) with an even number of carbon atoms.
5. The adhesive according to claim 1 or 2, wherein, The diol with an even number of carbon atoms (b1) is a polyol with 4 or fewer carbon atoms.
6. The adhesive according to claim 1 or 2, wherein, The bioplasticity of the polyester resin (i) is 60% or more.
7. An adhesive obtained by crosslinking an adhesive composition, said adhesive composition containing a polyester resin with a bioplasticity of 60% or more (ii). The polyester resin (ii) has structural sites derived from polycarboxylic acids (a) and structural sites derived from polyol components (b), and contains a diol (b1) with an even number of carbon atoms as the polyol component (b), wherein, Excluding dimer diols, The polyester resin (ii) has an ester group concentration of 2 mmol / g or higher, an acid value of 10 mg / KOH or lower, and a weight-average molecular weight greater than 50,000 and less than 500,000. The adhesive force (α) is 1 N / 25 mm or more under the following conditions. Adhesive strength (α): When an adhesive sheet with an adhesive layer formed by an adhesive on a substrate is made, the 180-degree peel strength of the adherend to the SUS-BA board after standing for 30 minutes at 23°C and 50%RH, at a peel speed of 300 mm / min, is expressed in N / 25 mm.
8. The adhesive according to any one of claims 1, 2, and 7, wherein, The adhesive composition also contains a hydrolysis inhibitor (iii).
9. The adhesive according to any one of claims 1, 2, and 7, wherein, The adhesive composition also contains a crosslinking agent (iv).
10. The adhesive according to any one of claims 1, 2, and 7, wherein, The adhesive composition also contains a tackifying resin (vii).
11. The adhesive according to any one of claims 1, 2, and 7, wherein, The bioplasticity of the adhesive is above 60%.
12. The adhesive according to any one of claims 1, 2 and 7, used for bonding components.
13. An adhesive sheet comprising an adhesive layer containing the adhesive according to any one of claims 1 to 12.
Citation Information
Patent Citations
Low moisture permeability pressure-sensitive adhesive sheet
JP2007308626A
Polyester, polyester composition, adhesive composition, adhesive layer, and adhesive sheet
JP2010037463A
Polyester adhesive composition and adhesive sheet
CN106170526A
